President’s Message: Basic Principles - Hill, Marlene (Operating Room Nurses Association of Canada Journal, 2000)
Recently, I attended a wonderful educational session during the American Operating Room Nurses’ Congress given by Hugh Gouldthorpe titled “I’ve Always Looked Up to Giraffes". It is only coincidental that his message is similar to mine. The following material was ready to be submitted to this Journal in March.